Innovation and technology for sustainable mining activity: A worldwide research assessment - Aznar-Sánchez, José A.; Velasco-Muñoz, Juan F.; Belmonte-Ureña, Luis J.; Manzano-Agugliaro, Francisco (Journal of cleaner production, 2019)
The analysis of innovations and technologies aimed at improving the sustainability of mining activity has become important in recent decades. The main objective of this article is to evaluate the dynamics of this line of research worldwide between 1998 and 2017. A bibliometric analysis and a systematic review of a sample of 2,562 articles was developed along with an analytical framework based on the mine life cycle and the three areas of sustainability (economic, social and environmental). The results show that sustainability research has grown at a much higher rate than that of mining and minerals research. The three journals that have published the most articles on this line of research are Journal of Cleaner Production, Environmental Science and Technology, and Gornyi Zhurnal, and the three countries with the highest number of published articles are the USA, China, and Germany. Some 60.9%, 30.9%, and 8.2% of the analysed mining innovations impact environmental, economic, and social sustainability, respectively, and some 7.1% affect the exploration phase, 84.8% the exploitation phase, and 8.1% the closure phase. The analysis of issues related to environmental sustainability becomes more relevant as the exploration phase moves on to exploitation and closure. The primary challenges and future lines of research are in reducing energy use and increasing the use of renewable sources, analysing the social sustainability of current mining activities, and achieving clean production in the development of new mining activity environments (ice-covered areas and the ocean floor). This work provides new perspectives on the analysis and integral assessment of innovations and technologies aimed at making mining activity more sustainable, particularly where the contributions to the environmental, economic, and social fields are valued. [Display omitted] •Innovation and technology are key factors for mining sustainability.•A systematic review and bibliometric analysis have been performed on 2562 articles.•Mining expansion to icy and ocean soil presents challenges to cleaner production.•The pending subject of mining activity related to sustainability is social field.